2011
DOI: 10.1002/gepi.20643
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of rare sequence variants: an overview of collapsing methods

Abstract: With the advent of novel sequencing technologies, interest in the identification of rare variants that influence common traits has increased rapidly. Standard statistical methods, such as the Cochrane-Armitage trend test or logistic regression, fail in this setting for the analysis of unrelated subjects because of the rareness of the variants. Recently, various alternative approaches have been proposed that circumvent the rareness problem by collapsing rare variants in a defined genetic region or sets of regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
148
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 144 publications
(148 citation statements)
references
References 33 publications
0
148
0
Order By: Relevance
“…This realization gave way to the search for missing heritability in the post-GWAS era wherein rare variants have been heralded to be an important key, as they were not genotyped in GWAS. This paradigm shift fueled with concurrent availability of the next-generation sequencing (NGS) data lead to burgeoning of methods for collectively analyzing rare single nucleotide variants (rSNV), typically referred as 'collapsing methods' [3,4]. Nonetheless, there are still many limitations associated with NGS data such as accuracy of genotype calling and cost, and as collapsing methods rely on these data solely, they inherit these limitations as well [5].…”
Section: Introductionmentioning
confidence: 99%
“…This realization gave way to the search for missing heritability in the post-GWAS era wherein rare variants have been heralded to be an important key, as they were not genotyped in GWAS. This paradigm shift fueled with concurrent availability of the next-generation sequencing (NGS) data lead to burgeoning of methods for collectively analyzing rare single nucleotide variants (rSNV), typically referred as 'collapsing methods' [3,4]. Nonetheless, there are still many limitations associated with NGS data such as accuracy of genotype calling and cost, and as collapsing methods rely on these data solely, they inherit these limitations as well [5].…”
Section: Introductionmentioning
confidence: 99%
“…Collapsing-based methods, without a doubt, constitute the predominant class, composed of most of the rare variant association methods proposed to date. [21][22][23][24][25] However, recent works have suggested that haplotyping-based methods may offer advantages and can be more powerful than collapsing methods for some underlying disease settings. 7,8,10 It is in that vein that hapKL is proposed to further explore the benefits of haplotypingbased approaches using existing common SNP data for detecting rare variants that are associated with common diseases without the need to rely on newer sequencing data.…”
Section: Discussionmentioning
confidence: 99%
“…However, indirect association testing assumes low-level allelic heterogeneity and assumes that the variants are common [21,44]. Rare variants have low MAF and low r 2 values and thus exhibit poor tagging properties with common variants (see Table 3) [21,51]. Inappropriate indirect SNP association testing runs a high risk of false-negative results because rare functional variants can be inadequately tagged.…”
Section: Current Methods To Analyze Low Frequency Variationmentioning
confidence: 99%